Typhochrestus acoreensis - Borges, Paulo A. V. (2021)
JUSTIFICATION: Typhochrestus acoreensis is a single-island endemic species, restricted to Terceira Island (Azores, Portugal) (Borges et al. 2010). It is a rare species, with a restricted Extent of Occurrence (EOO) (4-24 km² ) and Area of Occupancy (AOO) (4-24 km²), but it is likely to be at the upper end of this estimate. The species occurs in a single patch of native forest (at Biscoito da Ferraria Reserve). There is a continuing decline in the EOO, AOO, extent and quality of habitat as well as the number of mature individuals as a result of the invasions of non-native plants and the impact of Cryptomeria japonica plantations, with the destruction of the main original site. Therefore, we suggest as future measures of conservation: (1) a long-term monitoring plan of the species; (2) control of invasive species, and (3) avoid the expansion of Cryptomeria japonica plantations in the Pico Alto area. The species is assessed as Critically Endangered (CR).